Front and Back Matter for Volume 2 Issue 4, July 2025 - Trends in General Medicine; Public Health, Svāsthya (PT. Mega Science Indonesia, 2025)
Volume 2, Issue 4, July 2025 This issue consists of 5 articles contributed by 16 authors affiliated with 12 affiliations from four countries including Indonesia (Universitas Pembangunan Nasional Veteran Jakarta, Universitas Hindu Indonesia, Universitas Negeri Makassar, Universitas Hang Tuah Surabaya, Universitas Muhammadiyah Semarang, Universitas Jambi, dan Indonesian Society of Epidemiologists), United Kingdom (Royal Society of Tropical Medicine and Hygiene), Timor-Leste (Epidemiological Surveillance Municipal Health Service (SMS) Bobonaro, National University of Timor-Leste (UNTL), National Institute of Public Health of Timor-Leste (INSP-TL)), Thailand (Mahasarakham University)